Impact of Energy Consumption on Economic Growth of Malaysia: Crisis Effect - Kueh, Jerome; Hwang, Josephine Yau Tan; Liwan, Audrey (The journal of contemporary issues in business and government, 2021)
The study aims to examine the impact of energy consumption on the economic growth of Malaysia by considering the 1997 Asian Financial Crisis and 2009 Global Financial Crisis. Autoregressive distributed lag (ARDL) bounds testing method is adopted to estimate the long run and short run impact for the sample period from 1980 to 2019. Empirical findings show that energy consumption has a positive impact on the economic growth of Malaysia in the long run. Furthermore, the impact of energy consumption on growth intensifies during both financial crisis periods.